Plication for Severe Peyronie's Deformities Has Similar Long-Term Outcomes to Milder Cases. Issue 10 (15th September 2018) - Reddy, Rohit S.; McKibben, Maxim J.; Fuchs, Joceline S.; Shakir, Nabeel; Scott, Jeremy; Morey, Allen F.
Abstract: Introduction: Penile plication (PP) for Peyronie's disease (PD) is an established treatment option for mild to moderate curvature, but scant data exist regarding its utility in severe deformities. Aim: To evaluate long-term outcomes among men undergoing PP for PD, comparing severe to mild/moderate penile deformities. Methods: We performed a retrospective review of patients who underwent PP for PD between 2009 and 2017. All patients underwent multiple parallel tunical plication without degloving. Severe PD was defined as either curvature ≥60 degrees or biplanar curvature ≥35 degrees. Patient demographics and surgical outcomes were analyzed. A modified PD Questionnaire and International Index of Erectile Function (IIEF)-5 were administered by telephone. Main Outcome Measure: Long-term patient-reported outcomes were evaluated from a modified survey incorporating the PD Questionnaire and IIEF-5. Results: Of 327 PP patients, 102 (31%) responded to the telephone survey at a median 59.5 months (interquartile range 28.3–84) since surgery. Patients were equally distributed into severe (n = 51) and mild/moderate (n = 51) groups. Despite a greater mean degree of curvature in severe compared to mild/moderate patients (71.6 degrees vs 37.7 degrees, respectively, P < .001), correction of penile curvature was achieved in 91% of patients, with a mean change of 60.7 degrees in severe cases compared to 31.4 degrees in mild/moderate cases ( P < .001). Equal numbers of patients in severe and mild/moderate groups reported improvement of penile curvature (74.5% vs 74.5%, P = 1.0) and sexual function (51.0% vs 49.0%, P = .84). PD Questionnaire metrics were likewise similar between severe and mild/moderate patients ( P > .1), as were rates of subjective penile shortening (62.7% vs 62.7%, P = 1.0) and IIEF-5, both pre-operatively (19.5 vs 19.7, P = .9) and post-operatively (19.4 vs 17.6, respectively, P = .15). On multivariate logistic regression, worsening sexual function was significantly associated with increased age (odds ratio 1.07, P = .01) and pre-operative IIEF (odds ratio 1.14, P = .02). Clinical Implications: PP should be considered in PD patients with severe deformities, as outcomes are favorable and comparable to those with milder curvature. Strength & Limitations: This is a novel study evaluating long-term patient-reported outcomes after PP, comparing patients with severe deformity to those with mild/moderate curvature. The study was limited by retrospective design, relatively low survey response rate (31%), and lack of validated post-operative PD questionnaire. Conclusion: Long-term patient-reported outcomes of PP for severe PD deformities are comparable to mild/moderate cases, supporting broader application of PP beyond milder deformities.